Sekolah Tanpa Bullying : Membangun Empati Menciptakan Sekolah yang Inklusif dan Ramah - Jefry Crisbiantoro; Muh Ismar; M. Afiz Nurhaedi; Betram B; Retna Cahyani; Riby Desmita Sawendari; Indriyanti I; Sarni S; Luh Putu Kansiva Vionika; Nurul Syafika; Irma Afriani Lorensa; Nabila N (Yayasan Daarul Huda Kruengmane, 2026)
This research aims to describe the implementation of Stop Bullying Socialization activities at SDN 1 Andowengga and its impact on student behavior. Bullying is an aggressive action that can have a negative impact physically, emotionally, and socially, especially on elementary school students. This research uses a qualitative descriptive approach with the subject of class V–VI students. Socialization activities include interactive lectures, discussions, educational video screenings, role-playing, and Stop Bullying declarations. Data was collected through observation, interview, documentation, and questionnaire, then analyzed descriptively. Research results show that socialization succeeds in increasing students' understanding of bullying, fostering empathy, and encouraging mutual respect and caring behavior towards friends. The change in positive attitude can be seen from the reduction of small conflicts, increased cooperation, and the courage of students to report bullying behavior. The success of the activity is supported by the active involvement of teachers and principals, as well as an interactive approach that emphasizes direct experience. Although some challenges still arise, this activity is effective as a preventive and educational step in creating a safe, comfortable, and bullying-free school environment. Research results can be a model for other schools in the development of bullying prevention programs sustainably.